CHANGE OF AMERICAN MIGRATION POLICIES AND THE CONSEQUENCE OF INFLATION OF ASSIMILATION AMONG ARAB AMERICANS - Mohammed Yassin Mohd Aba Sha’ar; Nur Lailatur Rofiah (INJECT (Interdisciplinary Journal of Communication), 2017)
United States has been well known as the country of immigrants since 1492. Over the years, people used to migrate to the United States from all over the world in order to share the vantages of the ‘American Dream’. Arabs started their systematic migration to the United States in the 1870s. Initially they perceive themselves as immigrants whose aim is to earn economic amelioration. This article traces the history of Arab migration to the United States and exposes the multifarious push and pull-factors behind the migration of each wave. Constantly, the United States used to impose deliberate migration laws that aim to either to restrict or recruit immigrants from particular races and nationalities. Thereby, this paper reviews different legislations and policies that have been executed by American authorities in order to restrict or ban the Arab immigrants from migrating to the United States. Consequentially, such legislations contributed in the isolation of the Arab immigrants from the other worlds. AbstrakAmerika adalah dikenal sebagai negara imigran sejak tahun 1492. Bertahun-tahun orang-orang bermigrasi ke Amerika dari seluruh dunia untuk menikmati sebuah ‘Mimpi Amerika’. Orang Arab memulai migrasi yang sistematis ke Amerika tahun 1870-an. Awalnya mereka memandang diri sebagai pendatang yang bertujuan untuk mencapai perbaikan ekonomi. Makalah ini menelusuri sejarah migrasi orang Arab ke Amerika dan menjelaskan faktor tarik-menarik di balik gelombang migrasi. Seringkali Amerika memaksakan undang-undang migrasi yang bertujuan untuk membatasi atau merekrut imigran dari ras dan kebangsaan tertentu. Oleh karena itu, makalah ini mengulas peraturan perundang-undangan dan kebijakan yang berbeda yang dijalankan oleh pemerintah Amerika untuk membatasi imigran Arab agar tidak bermigrasi ke Amerika. Konsekuens undang-undang tersebut berkontribusi dalam mengisolasi imigran Arab dari negara lainnya.